Fuel Exemptions, Revenue Recycling, Equity and Efficiency: Evaluating Post-Kyoto Policies for Switzerland - Jan Imhof (Swiss Journal of Economics and Statistics, 2012)
The Swiss CO2 law runs out in 2012, together with the first commitment period of the Kyoto Protocol. Currently, the Swiss parliament is deciding on the successor of the law that aims to achieve a 20% reduction of CO2 emissions below 1990 levels by 2020. As a means to achieve this ambitious target, the current tax on stationary fuels at 36 CHF/t CO2 will be maintained, while transportation fuels will still be exempted from the carbon tax. Currently, the tax revenues are fully redistributed as a per-capita lump-sum payment via mandatory health insurance and to the employers proportional to their wage payments. This recycling scheme is likely to be prolonged. However, in the presence of the actual debate on the revision of the CO2 law, this paper reexamines the exemption of transportation fuels and the revenue recycling scheme under two points of view. First, I examine the effects on cost-effectiveness and second, I study their impact on equity. Using a static computable general equilibrium model of the Swiss economy incorporating 14 household groups, I find that tax exemptions increase the economy-wide costs of a carbon tax, yet fail to ease the effect on over-proportionally affected households. However, adjusting CO2 tax rates to correct for pre-existing fuel taxes that do not internalize any external effects may decrease the economy-wide cost of a green tax reform. On the other hand the choice of the recycling scheme has less of an effect on efficiency, but its impact on the distributional outcome of the tax reform has to be considered. Choosing an optimal, economy-wide tax will decrease overall costs considerably, while a lump-sum per-capita rebate will result in a progressive tax package at reasonable costs.
Keywords: D31; D58; H23; Q48; Q52; Q58; 330; Carbon Tax; Computable General Equilibrium; Double Dividend; Tax Exemptions; Climate Cent; Distributional Consequences